Założenia programowe jako kontekst kultury szkoły (w perspektywie prawdy i czasu) na przykładzie Polski i Ukrainy - Beata Adrjan (Problemy Wczesnej Edukacji)
In this article I have shown the programme assumption as part of school culture. Through Edgar Schein’s Model of Organizational Culture I have made an analysis of: programme, students’ book, and teachers’ book. I have compared them by interpretation based on the foundation of truth and time (from E. Schein Model). The result is that both school cultures have a similar foundation based on passing (time) and objectivism (truth). It means that our countries (Poland and Ukraine) after almost 25 years of freedom from soviet ideology up to now are at the same stage of thinking about school.